Five new species of Otacilia Thorell, 1897 (Araneae: Phrurolithidae) from the Wuling Mountain Range, China - Yao, Na; Irfan, Muhammad; Peng, Xianjin (Zootaxa, 2019)
Five new species of the genus Otacilia Thorell, 1897 from the Wuling Mountain Range in China are described here based on male and female specimens: O. acerosa sp. nov., O. lata sp. nov., O. palmata sp. nov., O. rulinensis sp. nov. and O. xingdoushanensis sp. nov.. Detailed morphological descriptions, photographs of the habitus and genital organs, line drawings, and locality maps are provided.